2020
DOI: 10.3892/etm.2020.9211
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is important in the pathogenesis of stress‑related mucosal disease

Abstract: Stress-related mucosal disease (SRMD) is a common complication in patients in the intensive care unit (ICU). The aim of the present study was to investigate the possible mechanisms for the pathogenesis of SRMD. In total, 38 patients with SRMD were enrolled from an ICU, as well as 15 healthy volunteers. The disease severity of patients in ICU was evaluated using the Acute Physiology and Chronic Health Evaluation (APACHE) II score. Gastric mucosa with the most severe lesions were biopsied for hematoxylin and eos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Due to excessive generation of free radicals, the body synthesizes uric acid in an attempt to mop-up the generated free radicals (18,19) . which are in agreement with the finding of (5,(20)(21)(22) .…”
Section: Discussionsupporting
confidence: 93%
“…Due to excessive generation of free radicals, the body synthesizes uric acid in an attempt to mop-up the generated free radicals (18,19) . which are in agreement with the finding of (5,(20)(21)(22) .…”
Section: Discussionsupporting
confidence: 93%
“… 40 The assessment of oxidative stress is mainly realized by the following two parameters: level of MDA, which is used as an indicator of lipid peroxidation; and activity of SOD, which reflects antioxidant capacity. 41 Our study showed that the activity of SOD in serum of the model group decreased significantly and the content of MDA increased significantly. The results showed that ischemic injury damaged the enzymatic antioxidant system, decreased the ability of scavenging free radicals, increased the production of free radicals, aggravated lipid peroxidation and caused brain damage.…”
Section: Discussionmentioning
confidence: 51%